2020
DOI: 10.1186/s12931-020-01402-3
|View full text |Cite
|
Sign up to set email alerts
|

T2 and T17 cytokines alter the cargo and function of airway epithelium-derived extracellular vesicles

Abstract: Background: Asthma is a common and heterogeneous disease that includes subgroups characterized by type 2 (T2) or type 17 (T17) immune responses for which there is a need to identify the underlying mechanisms and biomarkers in order to develop specific therapies. These subgroups can be defined by airway epithelium gene signatures and the airway epithelium has also been implicated to play a significant role in asthma pathology. Extracellular vesicles (EVs) carry functional biomolecules and participate in cell-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Protein enrichment analysis with reference to Gene Ontology (GO) "Cellular Component" sub-domain revealed that the PEx matrix is enriched in extracellular proteins associated with "exosome" (Figure 3, Table 2A). This nding is particularly interesting due to the emerging role of the exosomes as mediators of biomarkers for several chronic lung diseases [29,30]. In addition, based on results from the GO "Biological Processes" domain analysis, PEx proteome seem highly relevant for studies on the role of innate immune response in development of respiratory diseases and host defence.…”
Section: Discussionmentioning
confidence: 99%
“…Protein enrichment analysis with reference to Gene Ontology (GO) "Cellular Component" sub-domain revealed that the PEx matrix is enriched in extracellular proteins associated with "exosome" (Figure 3, Table 2A). This nding is particularly interesting due to the emerging role of the exosomes as mediators of biomarkers for several chronic lung diseases [29,30]. In addition, based on results from the GO "Biological Processes" domain analysis, PEx proteome seem highly relevant for studies on the role of innate immune response in development of respiratory diseases and host defence.…”
Section: Discussionmentioning
confidence: 99%
“…Structural lung cells, including airway epithelial cells (AECs) and airway smooth muscle cells (ASMCs), play pivotal roles in asthmatic disease and inflammation [ 207 , 208 ]. T2 cytokine-stimulated exosomes presented an increase in nitric oxide synthase 2 (NOS2), and exosomes from T17-stimulated epithelial cells showed a capacity for neutrophil chemotaxis.…”
Section: Exosomes From Other Cellular Populations Implicated In Asmentioning
confidence: 99%
“…Several studies by Woodruff and colleagues have demonstrated the ability of the airway epithelium to respond with unique gene and protein signatures in response to T2 cytokines, and that these signatures could be used as biomarkers for T2 asthma [ 177 , 178 , 179 ]. One of the proteins from this T2 signature is periostin, which is increased in epithelial cells in response to IL-13 +/− IL-4 [ 177 , 180 , 181 ], and which may have potential as a systemic biomarker of eosinophilic airway inflammation [ 182 , 183 ]. Periostin, a matricellular protein, has been implicated in processes related to airway remodeling such as cell proliferation, collagen production and epithelial-to-mesenchymal transition [ 184 ], as well as subepithelial fibrosis [ 185 ], mainly driven by TGF-β activation.…”
Section: The Effect Of T2 Inflammation On the Airway Epitheliummentioning
confidence: 99%
“…Higher levels of nitric oxide are usually linked to increased levels of inducible nitric oxide synthase (NOS2) in the airway epithelium, which can be normalized through the administration of corticosteroids [ 208 , 209 , 210 ]. Several cytokines can increase the levels of NOS2 on both the gene and protein level [ 208 , 210 ], though the effect is suggested to be stronger from T2 cytokines including IL-4 and IL-13 [ 181 , 211 ].…”
Section: The Effect Of T2 Inflammation On the Airway Epitheliummentioning
confidence: 99%
See 1 more Smart Citation